Analysis of the Implementation of Primary Health Service Integration (ILP) Cluster 1 (Health Center Management) - Samino; Agung; Wayan; Christina; Supriyanto, Eko (Jurnal Kesehatan Cendikia Jenius, 2025)
The implementation of Primary Health Care Integration (PHCI) is a strategic effort to improve the quality of health services; therefore, its implementation needs to be evaluated. This study aimed to analyze the implementation of PHCI Cluster 1 (health center management) at the Hajimena Public Health Center. This research employed a qualitative approach with a case study design, involving six informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and document review. The study was conducted from July 25 to August 14, 2025, and data analysis included data reduction, data display, and conclusion drawing, supported by source and method triangulation. The results showed that the input, process, and output components were generally implemented adequately; however, challenges remained in human resource distribution, the consistency of mini-workshop implementation, and the optimization of several management functions. Performance assessment indicated a moderate level of achievement. In conclusion, the implementation of PHCI has been carried out but requires strengthening in human resource management, routine monitoring activities, and managerial functions to enhance sustainable service quality.